Public beliefs on antibiotics and symptoms of respiratory tract infections among rural and urban population in Poland: a questionnaire study - Godycki-Cwirko, M; Cals, J; Francis, N; Verheij, T; Butler, C; Goossens, H; Zakowska, I; Panasiuk, L (Public Library of Science, 2014)
INTRODUCTION: General public views and expectations around the use of antibiotics can influence general practitioners' antibiotic prescribing decisions. We set out to describe the knowledge, attitudes and beliefs about the use of antibiotics for respiratory tract infections in adults in Poland, and explore differences according to where people live in an urban-rural continuum. MATERIAL AND METHODS: Face to face survey among a stratified random sample of adults from the general population. RESULTS: 1,210 adults completed the questionnaire (87% response rate); 44.3% were rural; 57.9% were women. 49.4% of rural respondents and 44.4% of urban respondents had used an antibiotic in the last 2 years. Rural participants were less likely to agree with the statement "usually I know when I need an antibiotic," (53.5% vs. 61.3% respectively; p = 0.015) and reported that they would consult with a physician for a cough with yellow/green phlegm (69.2% vs. 74.9% respectively; p = 0.004), and were more likely to state that they would leave the decision about antibiotic prescribing to their doctor (87.5% vs. 85.6% respectively; p = 0.026). However, rural participants were more likely to believe that antibiotics accelerate recovery from sore throat (45.7% vs. 37.1% respectively; p = 0.017). Use of antibiotic in the last 2 years, level of education, number of children and awareness of the problem of developing antimicrobial resistance predicted accurate knowledge about antibiotic effectiveness. CONCLUSIONS: There were no major differences in beliefs about antibiotics between urban and rural responders, although rural responders were slightly less confident in their knowledge about antibiotics and self-reported greater use of antibiotics. Despite differences in the level of education between rural and urban responders, there were no significant differences in their knowledge about antibiotic effectiveness.